2015
DOI: 10.1080/09168451.2014.991691
|View full text |Cite
|
Sign up to set email alerts
|

Screening of lactic acid bacteria that can form mixed-species biofilm with Saccharomyces cerevisiae

Abstract: Morinaga (2015) Screening of lactic acid bacteria that can form mixed-species biofilm with Saccharomycescerevisiae, Bioscience, Biotechnology, and Biochemistry, 79:4,[681][682][683][684][685][686]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Direct or physical interactions: In many cases, direct interactions and cell to cell attachments enable microorganisms to work cooperatively and form complex structures like a biofilm [43,44], which usually leads to an increased viability of the microbial community members and their resistance to stresses. For example, S. cerevisiae can significantly enhance the viability of the probiotic strain Lb.…”
Section: Nature Of Interactionsmentioning
confidence: 99%
“…Direct or physical interactions: In many cases, direct interactions and cell to cell attachments enable microorganisms to work cooperatively and form complex structures like a biofilm [43,44], which usually leads to an increased viability of the microbial community members and their resistance to stresses. For example, S. cerevisiae can significantly enhance the viability of the probiotic strain Lb.…”
Section: Nature Of Interactionsmentioning
confidence: 99%
“…Definitely, microbial co-culture, which includes growing two or more microorganisms in the same small space, has been addressed as a potential method for triggering cryptic pathways ( Selegato and Castro-Gamboa, 2023 ). A previous studies proved different types of microorganisms, such as Saccharomyces cerevisiae, a species of yeast, and Lactobacillus plantarum, a strain of probiotics, could form a mixed-species biofilm on a glass surface in liquid media to improve their capacity and endure challenging conditions ( Furukawa et al, 2015 , Nozaka et al, 2014 , Yin et al, 2019 ). A Recent study has demonstrated that, in co-culture, diffusible signal factor (DSF) or auto regulatory molecules can influence biofilm architecture, stress response, and polymyxins tolerance in P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…The biofilm formed by Oenococcus oeni during wine fermentation increases the tolerance to wine stress and improves functional performance with effective malolactic activities (Bastard et al, 2016). Previous studies proved that S. cerevisiae and Lactobacillus plantarum could form a mixed-species biofilm on a glass surface in liquid media (Nozaka et al, 2014;Furukawa et al, 2015). A mixed biofilm could therefore be the lifestyle for S. cerevisiae and LAB in TAFS community.…”
Section: Introductionmentioning
confidence: 99%